Cloud-based Multi-Modal Information Analytics : hands-on approach - Hiriyannaiah, Srinidhi; G M , Siddesh; K G, Srinivasa (Boca Raton : CRC Press/Taylor & Francis, 2023)
Cloud based Multi-Modal Information Analytics: A Hands-on Approach discusses the various modalities of data and provide an aggregated solution using cloud. It includes the fundamentals of neural networks, different types and how they can be used for the multi-modal information analytics. The various application areas that are image-centric and videos are also presented with deployment solutions in the cloud.
Includes references and index.
Keywords: Cloud Computing; Data Analytics; Deep Learning; Speech Analytics